Buried but unsafe – defoliation depletes the underground storage organ (USO) of the mesic grassland geophyte, Hypoxis hemerocallidea - Morris, Craig D (bioRxiv, 2021)
Abstract Mesic grasslands in South Africa (> 650 mm a-1 MAP) are rich in herbaceous forbs, which outnumber grass species by more than 5 to 1. Many of these forbs have underground storage units (USOs), such as thickened rootstocks, rhizomes, bulbs, or corms, that provide resources (non-structural carbohydrates, minerals, and water) enabling them to resprout after dry, frosty winters, and fire. However, despite their extensive biomass and reserves ostensibly protected underground, geophytic mesic grassland forbs can be severely depleted or extirpated by chronic trampling and grazing of their aerial parts by livestock. This study examined a possible explanation for forb demise in overgrazed grassland by investigating, in a pot trial, whether the growth of forbs and the size of their USOs are negatively affected by simulated green leaf loss. In a 2×2 factorial (clipped vs. unclipped x spring regrowth in the dark vs. light), five replicate plants of Hypoxis hemerocallidea, a common mesic grassland forb that resprouts from a corm, were subject to six severe (clipped to 80 mm) defoliations during the growing season and regrown in spring under full or restricted light to measure stored reserve contribution to regrowth. Defoliated plants were resilient to defoliation during the growing season, matching the total biomass production of unclipped plants, though cutting reduced the number of leaves by ¬60% and flowers by almost 85%. Spring regrowth on stored reserves equalled that from reserves plus concurrent photosynthesis, indicating the value of USOs for regrowth. However, there was a marked carry-over effect of previous season defoliation, resulting in a one-third reduction in shoot growth and 40% fewer inflorescence in spring. Crucially, corm mass was more than halved by clipping. Above-ground spring growth was linearly related to corm mass. It was concluded that buried stored reserves are not protected by recurrent disturbance to aerial plant parts and that continued diminishment of USOs under chronic disturbance by overgrazing or frequent mowing would weaken and likely eventually kill plants, reducing forb species richness. Lenient management by infrequent summer mowing or grazing at moderate stocking rates combined with periodic rotational full season resting and dormant-season burning is recommend to maintain the USOs and vigour of forbs in mesic grassland. Competing Interest Statement The authors have declared no competing interest.